ORGANIC FARMING METHODS USED IN THE PRODUCTION OF ORGANIC VEGETABLE - Joemar Dayham Javier; Maria Pia M Sison (Socio-Economics/Agribusiness Department, 2023)
Organic farming is a method of crop production through the natural process instead of using chemical-based pesticides and fertilizers. This study was conducted to identify the organic farming method used in producing organic vegetables in terms of the following: soil cultivation, animal husbandry, natural pesticides, biofertilizers, composting, crop rotation, cover crops, diversified crops, mulching, and seed treatments. Key Informant Interviews and surveys were used in data gathering, and descriptive statistics were used in data analysis. Results revealed that regardless of the farm size (small, medium, large), organic vegetable growers have practiced soil cultivation techniques such as ploughing, digging, furrowing, and hoeing. Other organic vegetable production practices, for instance, homemade organic pesticides, vermicomposting, crop rotation (legume/leafy), cover crops (grass), and mulching (dry leaves, plastic mulch) are commonly practiced among the three farm types. Moreover, only a few farms have practiced animal husbandry and biofertilizer application, while seed pelleting for seed treatment was obviously practiced by large farm types.Â Â Majority of the farms have diversified crops like lettuce, cabbage, eggplant, tomato, cauliflower, bitter gourd, cucumber, and herbs. It is noteworthy that success in organic vegetable production is greatly dependent on the timely implementation of effective cultural/production practices which enable growers to minimize, or totally avoid risks, thus to improve crop yield, farmers should focus on optimizing production/cultural practices.